2019
DOI: 10.1007/s12325-019-0890-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment Patterns Among Patients Initiating Small Molecule Kinase Inhibitor Therapies for Thyroid Cancer in the United States

Abstract: IntroductionLittle is known about real-world use of small molecule kinase inhibitors (SMKI) for advanced thyroid cancer in the United States. This study examined prescribing patterns of SMKI agents recommended by the National Comprehensive Cancer Center (NCCN).MethodsThis retrospective study used a national health insurance database to identify patients diagnosed with thyroid cancer during 1/1/2006–6/30/2016 and with prescription claims for NCCN-recommended SMKI during 1/1/2010–5/31/2016 whose first claim date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…RAI‐R DTC is an aggressive and often rapidly progressing disease, 1,2,5 and only approximately 36% to 53% of patients with RAI‐R DTC receive a second‐line therapy 18 . Thus, timely and precise treatment selection is crucial to maximize efficacy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…RAI‐R DTC is an aggressive and often rapidly progressing disease, 1,2,5 and only approximately 36% to 53% of patients with RAI‐R DTC receive a second‐line therapy 18 . Thus, timely and precise treatment selection is crucial to maximize efficacy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first and largest real-world study in the USA to evaluate outcomes of 1L lenvatinib therapy and post-lenvatinib therapy for patients with RAI-r DTC. After approval in 2015, lenvatinib replaced sorafenib as the most commonly prescribed 1L treatment for DTC, representing 43.4% and 66.7% of 1L treatment in 2015 and 2016, respectively [ 14 ]. These real-world data provide supporting evidence that when prescribed in the community setting, up to 64.8% of patients treated with lenvatinib in 1L experienced disease response (similar to that observed in the pivotal SELECT trial) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent administrative claims study from the USA demonstrated that lenvatinib is the most commonly prescribed first-line (1L) agent for the treatment of RAI-r DTC [ 14 ]. However, no real-world clinical outcomes for patients who receive 1L lenvatinib in the USA have been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of Lenvatinib has been also corroborated by quality-of-life (QOL) studies demonstrating the efficacy of this treatment [ 30 ], positioning it as first-line treatment [ 31 ].…”
Section: The Tki Approved Drugs In Thyroid Cancersmentioning
confidence: 99%